Artificial Intelligence as the Technological Basis of the Digital Transformation of Economy - Yershova, O. L.; Bazhan, L. I. (Statistics of Ukraine, 2021)
At the present stage of economic development, the ultimate goal of the strategies of any multinational company in the global market is to increase business efficiency, which is largely ensured by the development and implementation of modern technologies. Artificial intelligence for the subjects of international economic relations is a set of tools that provide digital transformation of business. The development of artificial intelligence can not only change the business, but also modify the format of the country’s competition in the world market. Under the influence of the development of artificial intelligence systems, there is an intensive diversification of objects of international trade in goods and services, which leads to a fundamental, radical renewal of production strategies of leading companies in each country. All this in the context of globalization makes it necessary to pay much attention to the intellectualization of the Ukrainian economy. In particular, this process involves the intensification of the use of the Internet, information and communication technologies, Internet of Things. Digital technologies have a significant impact on the development of traditional sectors of the economy and become an integral part of modern management systems in the public sector, industrial production, medicine, entrepreneurship, creating new business models. It actualizes research of theoretical and applied aspects of economy digitalization on the basis of the analysis possibilities of artificial intelligence application in various spheres of digital economy development. To research the development of economy digital transformation, a systematic approach was used, on the basis of which the possibilities of digitalization of individual sectors of the economy were analyzed. Economic and managerial relations, which mediate the processes of digital transformation, have identified and systematized the prerequisites for digitalization, taking into account the trend of increasing the country’s competitiveness. The leading role of artificial intelligence in the digital transformation of the economy is substantiated. Various aspects related to the issues of digital transformation of the economy are highlighted. Trends in the development of intellectualization process of economic sectors – industrial, business, public administration – are studied. The main drivers of digital transformation are considered, which will contribute to the sustainable development of each sector of the economy, and their synergy will increase the competitiveness of the national economy in world markets. The main directions of development of digitalization of the economy of Ukraine are outlined. Projects of digital transformation of Ukraine are considered. The importance of digital infrastructure platforms based on artificial intelligence has been identified. Two scenarios for the development of Ukraine’s digital economy are proposed for consideration.